Innate Immune Responses to Avian Influenza Viruses in Ducks and Chickens - Danyel Evseev; Katharine E. Magor (Veterinary Sciences, 2019)
Mallard ducks are important natural hosts of low pathogenic avian influenza (LPAI) viruses and many strains circulate in this reservoir and cause little harm. Some strains can be transmitted to other hosts, including chickens, and cause respiratory and systemic disease. Rarely, these highly pathogenic avian influenza (HPAI) viruses cause disease in mallards, while chickens are highly susceptible. The long co-evolution of mallard ducks with influenza viruses has undoubtedly fine-tuned many immunological host–pathogen interactions to confer resistance to disease, which are poorly understood. Here, we compare innate responses to different avian influenza viruses in ducks and chickens to reveal differences that point to potential mechanisms of disease resistance. Mallard ducks are permissive to LPAI replication in their intestinal tissues without overtly compromising their fitness. In contrast, the mallard response to HPAI infection reflects an immediate and robust induction of type I interferon and antiviral interferon stimulated genes, highlighting the importance of the RIG-I pathway. Ducks also appear to limit the duration of the response, particularly of pro-inflammatory cytokine expression. Chickens lack RIG-I, and some modulators of the signaling pathway and may be compromised in initiating an early interferon response, allowing more viral replication and consequent damage. We review current knowledge about innate response mediators to influenza infection in mallard ducks compared to chickens to gain insight into protective immune responses, and open questions for future research.